SPECIAL ALLOCATION FUNDS FOR FAMILY PLANNING AND MODERN CONTRACEPTIVE PREVALENCE RATE IN INDONESIA - Widiyastuti, Parti; Khoirunurrofik (Badan Kependudukan Dan Keluarga Berencana Nasional, 2024)
The annual increase in the Special Allocation Fund (DAK) for Family Planning (FP) reflects the government’s commitment to strengthening population control and family planning programs at the regional level, yet disparities in achieving modern contraceptive prevalence rates (mCPR) persist across regions. This study analyzes the relationship between FP-related DAK—specifically, physical DAK and Operational Assistance for Family Planning (BOKB)—and the prevalence of modern contraceptive use in Indonesia, using data from 508 districts/cities that received FP-related DAK from 2012 to 2021. Secondary data from the Ministry of Finance, the National Population and Family Planning Board (BKKBN), and Statistics Indonesia (BPS) were analyzed using the Kunatitati approach with the Panel-Instrumental Variable (Panel-IV) method, employing the Construction Cost Index as the instrumental variable. The results reveal that physical FP-related DAK is not significantly associated with an increase in mCPR, while BOKB demonstrates a positive and significant association with improved mCPR. These findings highlight the importance of strategically allocating budgets to BOKB programs to achieve effective population control objectives. The government is encouraged to ensure sustainable allocation of FP-related DAK, particularly BOKB, to districts/cities, alongside regular monitoring and evaluation to ensure funds are utilized effectively, disbursed timely, and aligned with performance outcomes.